Consequences of Adopting IFRS Accounting Standards in Member Countries of The Association of Southeast Asian Nations (ASEAN) - Rizal Setiawan Amin; Muarif Leo; Syarifuddin; Darwis Said (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research presents a comprehensive review of academic literature on the consequences of adopting accounting standards based on International Financial Reporting Standards (IFRS) in ASEAN member countries, covering the period from 2017 to 2025. The method used is a Systematic Literature Review (SLR), utilizing the PRISMA guidelines and a structured literature search strategy through the Publish or Perish 8 application. We analyzed 10 selected relevant empirical studies and classified them into three main economic consequence dimensions: 1) Foreign Direct Investment (FDI); 2) Earnings Quality; and 3) Value Relevance. The results of the literature review generally show that the adoption of IFRS has a positive and consistent impact on capital markets in ASEAN member countries. The main limitations of existing research were also identified and discussed to provide direction for future research agendas. Keywords: Adoption of IFRS, Foreign Direct Investment, Profit Quality, Value Relevance, ASEAN